The real agricultural revolution : the transformation of English farming, 1939-1985 - Brassley, Paul, 1946-; Harvey, David, 1970-; Lobley, Matt; Winter, Michael, 1955- (Boydell studies in rural history., 2021)
At the outbreak of the Second World War in 1939 British agriculture was largely powered by the muscles of men, women, and horses, and used mostly nineteenth-century technology to produce less than half of the country's temperate food. By 1985, less land and far fewer people were involved in farming, the power sources and technologies had been completely transformed, and the output of the country's agriculture had more than doubled. This is the story of the national farm, reflecting the efforts and experiences of 200,000 or so farmers and their families, together with the people they employed. But it is not the story of any individual one of them. We know too little about change at the individual farm level, although what happened varied considerably between farms and between different technologies. Based on an improbably-surviving archive of Farm Management Survey accounts, supported by oral histories from some of the farmers involved, this book explores the links between the production of new technologies, their transmission through knowledge networks, and their reception on individual farms. It contests the idea that rapid adoption of technology was inevitable, and reveals the unevenness, variability and complexity that lay beneath the smooth surface of the official statistics.